A customer journey perspective on service delivery system design: insights from healthcare. Issue 10 (29th November 2018) - Ponsignon, Frederic; Smart, Andi; Phillips, Laura
Abstract : Purpose: The purpose of this paper is to provide novel theoretical insight into service delivery system (SDS) design. To do so, this paper adopts a customer journey perspective, using it as a frame to explore dimensions of experience quality that inform design requirements. Design/methodology/approach: This study utilises UK Patient Opinion data to analyse the stories of 200 cancer patients. Using a critical incident technique, 1, 207 attributes of experience quality are generated and classified into 17 quality dimensions across five stages of the customer (patient) journey. Findings: Analysis reveals both similarity and difference in dimensions of experience quality across the patient journey: seven dimensions are common to all five journey stages, from receiving diagnosis to end of life care; ten dimensions were found to vary, present in one or several of the stages but not in all. Research limitations/implications: Limitations include a lack of representativity of the story sample and the impossibility to verify the factual occurrence of the stories. Practical implications: Adopting a patient journey perspective can improve the practitioner understanding of the design requirements of SDS in healthcare. The results of the study can be applied by managers to configure SDS that achieve a higher quality of patient care throughout the patient journey. Originality/value: This paper extends existing literature on SDS design by adopting a customer journey perspective, revealing heterogeneity in experience quality across the customer journey currently unaccounted for in SDS design frameworks. Specifically, the findings challenge homogeneity in extant SDS design frameworks, evidencing the need for multiple, stage-specific SDS design requirements.